2021
DOI: 10.1097/rlu.0000000000003577
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility and Therapeutic Potential of Combined Peptide Receptor Radionuclide Therapy With Intensive Chemotherapy for Pediatric Patients With Relapsed or Refractory Metastatic Neuroblastoma

Abstract: Background Recent evidence has demonstrated high expression of somatostatin receptors in neuroblastoma (NB) cells. Because of this, we endeavored to evaluate the diagnostic performance and clinical efficacy of 68Ga-DOTATATE PET/CT and peptide receptor radionuclide therapy (PRRT) using 177Lu-DOTATATE combined with chemotherapy in pediatric NB patients. Patients and Methods In total, 14 pediatric patients with histopathologically confirmed NB underwent 68… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 39 publications
0
12
0
Order By: Relevance
“…(2,10,11,13,16,20,92,102,135,245,262). In studies on non-CNS tumors, PRRT has been successful both when used alone (4,11,20,21,42,73,74) and in combination with other cytotoxic therapies, including chemotherapy (284,(305)(306)(307)(308)(309). Third, the BnR ectopic expression/overexpression by these tumors can be used also for targeted delivery of cytotoxic non-radiolabeled compounds including chemotherapeutic agents, which is increasingly being studied in other malignant tumors (4,10,13,42,74,78,79).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…(2,10,11,13,16,20,92,102,135,245,262). In studies on non-CNS tumors, PRRT has been successful both when used alone (4,11,20,21,42,73,74) and in combination with other cytotoxic therapies, including chemotherapy (284,(305)(306)(307)(308)(309). Third, the BnR ectopic expression/overexpression by these tumors can be used also for targeted delivery of cytotoxic non-radiolabeled compounds including chemotherapeutic agents, which is increasingly being studied in other malignant tumors (4,10,13,42,74,78,79).…”
Section: Discussion/conclusionmentioning
confidence: 99%
“…Although there are a few published reports on the use of amino acid infusions in children for renal protection during PRRT, these describe significant variations in the infusional volume, the type of amino acids used, and the duration of the infusion [4,10,12,27,28]. While no immediate renal toxicity was reported in any of the publications, most of the reports did not include the cumulative radiation dose to the kidneys, which is predictive of late-onset renal disease [29].…”
Section: Clinical Practice For Administration Of Intravenous Fluids I...mentioning
confidence: 99%
“…Large randomised trials using PRRT in adults with neuroendocrine tumours have demonstrated survival and quality of life benefits [6][7][8][9]. There is increasing use of labelled SSTR analogues in paediatric neuroendocrine tumours including neuroblastomas [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…Another interesting research in the field was recently published by Fathpour et al, who evaluated the feasibility of PRRT with 177 Lu-DOTATATE in 14 children with histologically proven and therapy-refractory NB, some of whom had previously received chemotherapy [44]. All subjects were submitted to PET/CT with 68 Ga-DOTATATE, which resulted positive in 10 out of 14 cases and detected a median number of 2 lesions per patient.…”
Section: Somatostatin Receptor-targeted Theranosticsmentioning
confidence: 99%